Azathioprine promotes intestinal epithelial cell differentiation into Paneth cells and alleviates ileal Crohn’s disease severity - Ragab, Mohab; Schlichting, Heidi; Hicken, Maren; Mester, Patricia; Hirose, Misa; Almeida, Larissa N.; Christiansen, Lea; Ibrahim, Saleh; Tews, Hauke Christian; Divanovic, Senad; Sina, Christian; Derer, Stefanie (Scientific reports, 2024)
Paneth cells (PCs), a subset of intestinal epithelial cells (IECs) found at the base of small intestinal crypts, play an essential role in maintaining intestinal homeostasis. Altered PCs function is associated with diverse intestinal pathologies, including ileal Crohn’s disease (CD). CD patients with ileal involvement have been previously demonstrated to display impairment in PCs and decreased levels of anti-microbial peptides. Although the immunosuppressive drug Azathioprine (AZA) is widely used in CD therapy, the impact of AZA on IEC differentiation remains largely elusive. In the present study, we hypothesized that the orally administered drug AZA also exerts its effect through modulation of the intestinal epithelium and specifically via modulation of PC function. AZA-treated CD patients exhibited an ileal upregulation of AMPs on both mRNA and protein levels compared to non-AZA treated patients. Upon in vitro AZA stimulation, intestinal epithelial cell line MODE-K exhibited heightened expression levels of PC marker in concert with diminished cell proliferation but boosted mitochondrial OXPHOS activity. Moreover, differentiation of IECs, including PCs differentiation, was boosted in AZA-treated murine small intestinal organoids and was associated with decreased D-glucose consumption and decreased growth rates. Of note, AZA treatment strongly decreased Lgr5 mRNA expression as well as Ki67 positive cells. Further, AZA restored dysregulated PCs associated with mitochondrial dysfunction. AZA-dependent inhibition of IEC proliferation is accompanied by boosted mitochondria function and IEC differentiation into PC.